2016
DOI: 10.1074/jbc.m116.742171
|View full text |Cite
|
Sign up to set email alerts
|

Orai1 and TRPC1 Proteins Co-localize with CaV1.2 Channels to Form a Signal Complex in Vascular Smooth Muscle Cells

Abstract: Voltage-dependent Ca1.2 L-type Ca channels (LTCC) are the main route for calcium entry in vascular smooth muscle cells (VSMC). Several studies have also determined the relevant role of store-operated Ca channels (SOCC) in vascular tone regulation. Nevertheless, the role of Orai1- and TRPC1-dependent SOCC in vascular tone regulation and their possible interaction with Ca1.2 are still unknown. The current study sought to characterize the co-activation of SOCC and LTCC upon stimulation by agonists, and to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Our study not only confirms the existence of SOCE in SVZ cells, but also shows that in addition to Orai1, SVZ cells also possess TRPC1, as do embryonic brain stem cells from which adult NSC derive . In addition to supporting calcium entries, SOC have been shown to activate voltage‐gated channels in vascular cells . A previous electrophysiological study and our recordings (data not shown) indicate that SVZ stem cells are highly polarized and fail to produce action potentials.…”
Section: Discussionsupporting
confidence: 84%
“…Our study not only confirms the existence of SOCE in SVZ cells, but also shows that in addition to Orai1, SVZ cells also possess TRPC1, as do embryonic brain stem cells from which adult NSC derive . In addition to supporting calcium entries, SOC have been shown to activate voltage‐gated channels in vascular cells . A previous electrophysiological study and our recordings (data not shown) indicate that SVZ stem cells are highly polarized and fail to produce action potentials.…”
Section: Discussionsupporting
confidence: 84%
“…A well-known depolarizing TRP channel is TRPM4, which has been found to depolarize T lymphocytes [95]. Membrane depolarization induced by TRPC channel gating has been associated to a functional activation of voltage-dependent Ca 2+ channels in electrically excitable cells [96,97]. In addition, depolarization evoked by Ca 2+ and Na + influx through TRPC channels leads to subsequent attenuation of the driving force for Ca 2+ entry via Orai1 channels.…”
Section: Modulation Of Orai1 Function By Trpc Channelsmentioning
confidence: 99%
“…Kwan et al 18) reported that TRPC1 and BK Ca colocalize in VSMCs, and Ca 2+ influx through TRPC1 activates BK Ca to induce membrane hyperpolarization. Ávila-Medina et al 19) reported that TRPC1 and Orai1 co-localize with voltage-dependent Ca V 1.2 L-type Ca 2+ channels, and 5-HTinduced TRPC1-dependent SOCE can trigger the activation of voltage-dependent Ca V 1.2 L-type Ca 2+ channels. Therefore, it might still be worthwhile continuing to determine the effect of DHA on TRPC1 function in VSMCs.…”
Section: Discussionmentioning
confidence: 99%